2002
DOI: 10.1207/s15328031us0104_02
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning Variation in Multilevel Models

Abstract: Abstract.In multilevel modelling, the residual variation in a response variable is split into component parts that are attributed to various levels. In applied work, much use is made of the percentage of variation that is attributable to the higher-level sources of variation. Such a measure however only makes sense in simple variance components, Normal response, models where it is often referred to as the 'intra-unit correlation'. In this paper we describe how similar measures can be found for both more comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
607
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 731 publications
(619 citation statements)
references
References 3 publications
(1 reference statement)
2
607
0
10
Order By: Relevance
“…These values indicate the proportional amount of error of prediction reduced from the unconditional model to the final model at the within-person level [30]. To establish these values for the binary variable of lapse occurrence, an approximation of the level 1 variance term was established by treating lapse occurrence as a continuous variable [31].…”
Section: Resultsmentioning
confidence: 99%
“…These values indicate the proportional amount of error of prediction reduced from the unconditional model to the final model at the within-person level [30]. To establish these values for the binary variable of lapse occurrence, an approximation of the level 1 variance term was established by treating lapse occurrence as a continuous variable [31].…”
Section: Resultsmentioning
confidence: 99%
“…An initial multilevel model with no predictors indicated that ϳ13% of the variation in the odds of insurance adequacy may be attributable to differences among states, as estimated by using the latent variable approach described by Goldstein et al 16,17 Adjusting …”
Section: Resultsmentioning
confidence: 99%
“…Browne et al, 2005;Goldstein et al, 2002;Li J et al, 2008;Merlo et al, 2006b;Snijders & Bokser, 1999), as follows:…”
Section: The Variance Partition Coefficient (Vpc)mentioning
confidence: 99%